Pelembagaan Proses Pengajuan Keberatan Masyarakat Atas Pelaksanaan Penataan Ruang Kota - Andi Oetomo (The Institute for Research and Community Services, Institut Teknologi Bandung, 1995)
The implementation of urban planning in Indonesia tends to be oriented at the abuse public right to gain legal ownership over land. Land clearance and redevelopment and unilateral action by the government to change the land-use often creates problems. Ironically, almost all of those controversial actions are conducted on behalf of development, especially the implementation of city plan. This condition would not have been this severe had the public participation process in development planning been institutionalized. If we learn from experiences of some developed countries like United Kingdom and Australia, people who have been involved in city planning are still given the chance to address their complaints about the city plan and its implementation through court. Some forms of courts have been recognized in some developed countries for the public to complaints The city plan, and this has been an integral part of their spatial planning law. In Indonesia, these complaints and appeals have recently been channeled through PTUN.